3x2 + 10x +3
=> 3x2 + 9x +x +3
=> (3x2 +x )+ ( 9x +3)
=> x(3x +1) +3( 3x+1)
=>(3x+1) (x+3)
Tự làm tiếp nhé
a, ta có: 3x^2 +10x+3= 3x^2 + 9x +x +3 = 3x(x+3)+(x+3)=(x+3)+(3x+1)
2 câu còn lại đang trong qtrinhf suy nghĩ
a) \(3x^2+10x+3=3x^2+9x+x+3\)
\(=3x\left(x+3\right)+\left(x+3\right)\)
\(=\left(x+3\right)\left(3x+1\right)\)
b)\(5x^2+14x-3=5x^2+15x-x-3\)
\(=5x\left(x+3\right)-\left(x+3\right)\)
\(=\left(5x-1\right)\left(x+3\right)\)
c)\(6x^2+7x-3=6x^2+9x-2x-3\)
\(=3x\left(2x+3\right)-\left(2x+3\right)\)
\(=\left(3x-1\right)\left(2x+3\right)\)